2021
DOI: 10.1101/2021.12.06.471425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

XopQ induced stromule formation inNicotiana benthamianais causally linked to ETI signaling and depends on ADR1 and NRG1

Abstract: In Nicotiana benthamiana, expression of the Xanthomonas effector XopQ triggers ROQ1-dependent ETI responses and in parallel accumulation of plastids around the nucleus and the formation of stromules. Both processes were proposed to contribute to ETI-related hypersensitive cell death and thereby to plant immunity. Whether these reactions are directly connected to ETI signaling events has not been tested. Here we utilized transient expression experiments to determine whether XopQ-mediated plastid reactions are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Several following studies also showed that ETI-induced cell death was sometimes segregated from plant immunity (Glocova et al, 2005;Menna et al, 2015;Pitsili et al, 2020;Yang et al, 2022). Recently, the Xanthomonas effector XopQ-triggered immune responses were found to be separated from ETI-induced cell death in N. benthamiana (Prautsch et al, 2023). In the present study, RipAW C177A and RipAW's derivatives triggered plant immunity to restrict bacterial infection without inducing ETI-triggered cell death, which is consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Several following studies also showed that ETI-induced cell death was sometimes segregated from plant immunity (Glocova et al, 2005;Menna et al, 2015;Pitsili et al, 2020;Yang et al, 2022). Recently, the Xanthomonas effector XopQ-triggered immune responses were found to be separated from ETI-induced cell death in N. benthamiana (Prautsch et al, 2023). In the present study, RipAW C177A and RipAW's derivatives triggered plant immunity to restrict bacterial infection without inducing ETI-triggered cell death, which is consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…We next tested PTI responses initiated by LRR‐RLK Nb FLS2 in Nb mutant lines deficient in EDS1 complexes or RNLs, including an Nb nrg1 adr1 double mutant (Fig. 1d; Prautsch et al ., 2021). A reduced ROS burst in bak1 plants was not detected when using saturating flg22 concentrations (50 nM; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1 and Table S1. The Nb adr1 nrg1 double mutant line is described in more detail elsewhere (Prautsch et al ., 2021). Nb plants were cultivated in a glasshouse with a 16 h : 8 h, light : dark photoperiod (sunlight and/or IP65 lamps (Philips) equipped with Agro 400 W bulbs (SON‐T); 130–150 μE m −2 s −1 ; switchpoint; 100 μE m −2 s −1 ), 60% relative humidity (RH) at 24°C : 20°C, day : night.…”
Section: Methodsmentioning
confidence: 99%
“…Arabidopsis EDS1-PAD4-ADR1 have extensive "basal resistance" functions (weak ETI TNL , bolstering of PTI or yet further distinct function). By contrast, in N. benthamiana, immune functions of EDS1-PAD4 were not detected [47], and ADR1 appears to have a minor role [26,73]. Rather, EDS1-SAG101-NRG1 execute immune functions limited to ETI TNL [47].…”
Section: Evolution Of Pti-eti Immune Sectors and Connectionsmentioning
confidence: 90%